2015
DOI: 10.3807/josk.2015.19.5.508
|View full text |Cite
|
Sign up to set email alerts
|

Highly Flexible Touch Screen Panel Fabricated with Silver Nanowire Crossing Electrodes and Transparent Bridges

Abstract: A capacitive-type touch screen panel (TSP) composed of silver nanowire (AgNW) crossing electrodes and transparent bridge structures was fabricated on a polycarbonate film. The transparent bridge structure was formed with a stack of Al-doped ZnO (AZO) electrodes and SU-8 insulator. The stable and robust continuity of the bridge electrode over the bridge insulator was achieved by making the side-wall slope of the bridge insulator low and depositing the conformal AZO film with atomic layer deposition. With an ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…Touch screens can be classified into several types according to their sensing methods, [ 1,3 ] and of these, capacitive sensing has been widely used due to its durability, performance, simultaneous multitouch and highly sensitive sensing capabilities. [ 1,4–7 ] In capacitive sensing, the touch location of the finger or stylus can be determined by scanning for a change in capacitance at each location. Electrode arrays are arranged in two sheets of film with each of the X and Y axes, and these two axes can be used as driving (or transmitter) and sensing (or receiver) electrodes, respectively.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…Touch screens can be classified into several types according to their sensing methods, [ 1,3 ] and of these, capacitive sensing has been widely used due to its durability, performance, simultaneous multitouch and highly sensitive sensing capabilities. [ 1,4–7 ] In capacitive sensing, the touch location of the finger or stylus can be determined by scanning for a change in capacitance at each location. Electrode arrays are arranged in two sheets of film with each of the X and Y axes, and these two axes can be used as driving (or transmitter) and sensing (or receiver) electrodes, respectively.…”
Section: Figurementioning
confidence: 99%
“…However, in the case of bridge electrode patterning, a large amount of deposited material should be removed due to the small dimensions of the bridge electrodes, which results in a huge waste of materials. [ 7 ] In addition, a low yield can occur due to process difficulties. To overcome such problems, a proper fabrication method should be developed for bridge electrodes, which has been a critical issue for TSP manufacturers.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…techniques are compatible with low-energy deposition process and without any vacuum equipment. Direct laser ablation [13,75], shadow mask [11], chemical etching using the photolithography process [76] are all the patterning strategies for flexible transparent electrodes.…”
Section: Flexible Electronicsmentioning
confidence: 99%
“…As a pivotal component of many photoelectric products described by Chung et al [1] including solar cells studied by Yang et al [2], liquid crystal displays (LCDs) reported by Blake et al [3], organic light-emitting diodes(OLEDs) shown by Wu et al [4] and touch screen panels (TSPs) discussed by Jeon et al [5] and Kim et al [6], conductive electrodes have attracted more and more attention. Indium tin oxide (ITO) is the most widely used transparent conductive electrode material owing to its excellent optoelectronic properties.…”
Section: Introductionmentioning
confidence: 99%